Association of Autoantibodies to BP180 with Disease Activity in Greek Patients with Bullous Pemphigoid. (27th November 2012) - Patsatsi, Aikaterini; Kyriakou, Aikaterini; Pavlitou-Tsiontsi, Aikaterini; Giannakou, Anastasia; Sotiriadis, Dimitrios
Abstract : 39 bullous pemphigoid (BP) patients were studied to assess the clinical significance of anti-BP180 and anti-BP230 circulating autoantibodies of BP and correlate their titers with the clinical scores of the BP Disease Area Index (BPDAI) and the Autoimmune Bullous Skin Disorder Intensity Score (ABSIS) as well as with the intensity of pruritus measured by the BPDAI pruritus component. All parameters were evaluated by the time of diagnosis (baseline), month 3, and month 6. Titers of anti-BP180 autoantibodies were strongly correlated with BPDAI (r = 0.557, P   value < 0 .0001 ) and ABSIS (r = 0.570, P   value < 0 .0001 ) values, as well as with BPDAI component for the intensity of pruritus (rho = 0 .530, P   value = 0 .001 ) at baseline. At month 3, titers of anti-BP180 autoantibodies were strongly correlated with BPDAI (rho = 0 .626, P   value = 0 .000 ) and ABSIS (rho = 0 .625, P   value = 0 .000 ) values, as well as with the BPDAI component for the intensity of pruritus (rho = 0 .625, P   value = 0 .000 ). At month 6, titers of anti-BP180 autoantibodies were strongly correlated with BPDAI (rho = 0 .527, P   value = 0 .001 ) and ABSIS (rho = 0 .526, P   value = 0 .001 ) values, as well as with the BPDAI component for the intensity of pruritus (rho = 0 .525, P   value = 0 .001 ). There was no statistically significant correlation between titers of anti-BP230 autoantibodies and the BPDAI, ABSIS, and BPDAI component for the intensity of pruritus at the same time points.